AB1290 Ultrasound evaluation correlates with disease activity in RA patients: Results of the SONAR-SCQM database. (23rd January 2014) - Zufferey, P.; Bruhlart, L.; Tamborrini, G.; Scherer, A.; Ziswiler, H.R.
Abstract : Background: Ultrasound has been shown to be more sensitive than clinical examination for detecting synovitis and many studies have shown that it can be a reliable tool for monitoring RA patients. There are however few reports on its use in common practice, outside studies and or specialized centers. Since 2008, the Swiss Sonography in Arthritis and Rheumatism (SONAR) group has developed a reproducible semi-quantitative score for RA using OMERACT criteria for synovitis. The score includes B mode and Doppler mode. The score has been learned by 70 rheumatologists and since 2009 included as a routine evaluation tool in the Swiss SCQM RA cohort. Objectives: To evaluate the correlation between the ultrasound scores and conventional outcome measures of disease activity (DAS28ESR or DAS28CRP) in the RA patients. Methods: The SONAR score includes a semi-quantitative B mode and Doppler evaluation of metacarpo-phalangeal and proximal interphalangeal joints 2 to 5, wrist, elbows and knees (22 joints, grade: 0 to 3, t maximum of 66 points each). From January 2009 to January 2012, 508 patients included in the SCQM registry had at least one SONAR evaluation. Only the first available visit was analysed. Simultaneous DAS28 assessments were available in 337 patients for DAS28ESR, in 345 for DAS28CRP. Analysis comprised Pearson correlation between b mode and Doppler score compared to DAS28ESR and DAS28CRP values. We also analysed the SONAR scores within the classical categories of DAS activity: remission (<2.6), low disease activity (>2.6<3.2), moderately active disease(>3.2<5), very active disease(>5). Results: There was a moderate significant linear correlation between the SONAR B mode score and clinically assessed disease activity: (Pearson coefficient r: 0.43 for DAS-ESR, r: 0.39 for DAS-CRP). The same was true for the SONAR Doppler score (Pearson r: 0.37 for DAS-ESR, r: 0.39 for DASCRP). Although, the mean SONAR scores (both b-mode and Doppler) differed significantly (p<0.05) within categories of DAS, except for the low and moderate active disease groups, the individual scores were largely overlapping with some discrepancies (see table below). Conclusions: The SONAR ultrasound score can be used in daily clinical practice by practicing rheumatologists and correlates with clinical measures of disease activity. However, on an individual level, many discrepancies and overlapping results exist, especially among patients with low or moderate active disease. The significance of these discrepancies, in particular the persistence of US synovitis in patients clinically in remission or low disease activity, needs to be further evaluated in a longitudinal study. Disclosure of Interest: None Declared